LA INSUFICIENTE SANCIÓN DE LA LEY DE GESTIÓN AMBIENTAL PERMITE A PERSONAS NATURALES Y JURÍDICAS VULNERAR EL BUEN VIVIR, SUMAK KAWSAY - Carrión Pacheco, Luis Israel (2015)
Protection of the right to a healthy environment is one of the provisions referred to in the current Constitution of the Republic of the Ecuador, with the aim of guaranteeing the defense of all those social, cultural and natural elements that are part of the environment, including the population, whose constitutional section in Art. 14, recognizes the right of the population to live in a healthy environment and ecologically balanced, to ensure sustainability and good living, sumak kawsay. Certainly the life of the human being, its economic and productive development system they depend on nature environmental services, to secure our present and future, well-being is deben progressively eliminate the negative environmental impacts avoiding the generation of pollution. The continuous improvement of the environmental performance allows you to maintain the corresponding harmony between the environment and society. It is important to establish that the action of natural or legal persons carrying out business or industrial activities is an important element in order to avoid environmental damage and if produced, take necessary measures to deal with the problem, however against the omission to situations that may cause or are causing environmental damage to the ecosystems of report about it to the Ministry of industry or institutions of the sectional regime self-employed we have an environmental management act obsolete inadequately sanctioning this situation attempted.